2017
DOI: 10.1590/0034-737x201764040003
|View full text |Cite
|
Sign up to set email alerts
|

Yield and nutritional efficiency of corn in response to rates and splits of nitrogen fertilization

Abstract: Despite its relevance, nitrogen is poorly utilized by the plants when improperly applied. Thus, the objective of this study was to evaluate the yield and nitrogen use efficiency (NUE) in corn in response to doses and split application of nitrogen fertilization. The experimental design was a randomized block design, with three replications. Doses of nitrogen of 0, 30, 60 and 180 kg ha -1 were applied at sowing in order to create different nutritional status of corn plants and to obtain different values of Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
0
0
1
Order By: Relevance
“…The low PE indicates that accumulation of nutrients (input) was higher than the grain yield (output). Amado et al, (2017) observed PEN was higher when N application rates were low and it decreased as N levels increased, similar to our findings. The researchers recorded PEN value of 40 kg kg -1 from the application of N@180 kg ha -1 , which is comparable to our report, which obtained PEN value of 43.4 kg kg -1 at the same rate of nitrogen application.…”
Section: Physiological Efficiencysupporting
confidence: 92%
“…The low PE indicates that accumulation of nutrients (input) was higher than the grain yield (output). Amado et al, (2017) observed PEN was higher when N application rates were low and it decreased as N levels increased, similar to our findings. The researchers recorded PEN value of 40 kg kg -1 from the application of N@180 kg ha -1 , which is comparable to our report, which obtained PEN value of 43.4 kg kg -1 at the same rate of nitrogen application.…”
Section: Physiological Efficiencysupporting
confidence: 92%
“…Já os autores Grohs, Mundstock & Poletto (2009), Motomiya (2009) e Machado (2015) afirmam que há correlação entre o NDVI e fatores como: mofo-branco, no artigo publicado por Machado (2015), potencial produtivo de trigo e cevada no trabalho de Grohs, Mundstock & Poletto (2009), e a deficiência de N em algodoeiros, em resultado da pesquisa de Motomiya (2009). No caso específico do milho e sua relação com o nutriente N, o NDVI é comumente utilizado, e o sensor GreenSeeker tem especial relevância no assunto, sendo utilizado em trabalhos como o de Amado et al (2017), que avaliaram no seu trabalho a resposta da produtividade do milho e eficiência de aplicação de N no sul paraguaiano, onde os mesmos observaram o acréscimo do valor de NDVI após a aplicação do N do estágio V8 para V12 da planta, e no trabalho de Walsh (2015) que citou em seu trabalho a experiência de produtores que fizeram uso do sensor GreenSeeker para melhor manejar a aplicação de N em Idaho nos Estados Unidos.…”
Section: Resultsunclassified
“…Maize crop responses to N fertilizer application are variable and depend on several factors, such as the management system adopted (conventional, no-tillage, and crop rotation), the previous crop, the use of hybrids, the region (climate, soil, and altitude) and the planting season. The literature shows different results, with the highest maize yields obtained under N rates of 20 to 90 kg ha -1 (Simão et al, 2021), 60 to 120 kg ha -1 (Amado et al, 2017), 0 to 180 kg ha -1 (Ahmad et al, 2020) or even 250 kg ha -1 (Lyra et al, 2014) applied as topdressing.…”
Section: Introductionmentioning
confidence: 98%